2020
DOI: 10.3389/fbioe.2020.00771
|View full text |Cite
|
Sign up to set email alerts
|

Effective Harvesting of Nannochloropsis Microalgae Using Mushroom Chitosan: A Pilot-Scale Study

Abstract: For efficient downstream processing, harvesting remains as one of the challenges in producing Nannochloropsis biomass, a microalga with high-value omega-3 oils. Flocculation is an effective, low-energy, low-cost method to harvest microalgae. Chitosan has been shown to be an effective food-grade flocculant; however, commercial chitosan is sourced from crustaceans, which has disadvantages including concerns over heavy-metal contamination. Thus, this study tests the flocculation potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…with over 99% efficiency (Chua et al, 2019). Nannochloropsis oceanica cultivated in a 2000 L raceway pond was harvested using mushroom chitosan at 25 ppm (Chua et al, 2020).…”
Section: Flocculationmentioning
confidence: 99%
See 1 more Smart Citation
“…with over 99% efficiency (Chua et al, 2019). Nannochloropsis oceanica cultivated in a 2000 L raceway pond was harvested using mushroom chitosan at 25 ppm (Chua et al, 2020).…”
Section: Flocculationmentioning
confidence: 99%
“…with over 99% efficiency (Chua et al, 2019). Nannochloropsis oceanica cultivated in a 2000 L raceway pond was harvested using mushroom chitosan at 25 ppm (Chua et al, 2020). The flocculant was mixed for 10 min using an airlift system, followed by settling for 24 h, to obtain biomass‐containing EPA up to 41.3 (±0.3)% of TFA, with a flocculation efficiency of 73%.…”
Section: Downstream Processing Strategies For the Valorization Of The...mentioning
confidence: 99%
“…A study showed that mushroom chitosan could be an efficient flocculating agent with more than 95% efficiency for Nannochloropsis spp. [221] Other alternatives include Moringa oleifera seed extract, which has been proven to be an effective coagulating agent for removing Chlorella, Microcystis, Oocystis, and Scenedesmus. [222] Combinations of harvesting techniques are often used to reduce the overall cost of the harvesting process.…”
Section: Biomass Harvestingmentioning
confidence: 99%
“…(Dixon and Wilken, 2018), diatoms (Bacillariophyceae), 12 Nannochloropsis spp. (Chua et al, 2020), Schizochytrium spp. (EFSA NDA Panel, 2020), Crypthecodinium spp.…”
Section: Microalgaementioning
confidence: 99%